γδ T Cells Are Required for Pulmonary IL-17A Expression after Ozone Exposure in Mice: Role of TNFα - Mathews, Joel A. (Public Library of Science, 2014)
Ozone is an air pollutant that causes pulmonary symptoms. In mice, ozone exposure causes pulmonary injury and increases bronchoalveolar lavage macrophages and neutrophils. We have shown that IL-17A is important in the recruitment of neutrophils after subacute ozone exposure (0.3 ppm for 24–72 h). We hypothesized that γδ T cells are the main producers of IL-17A after subacute ozone. To explore this hypothesis we exposed wildtype mice and mice deficient in γδ T cells (TCRδ(−/−)) to ozone or room air. Ozone-induced increases in BAL macrophages and neutrophils were attenuated in TCRδ(−/−) mice. Ozone increased the number of γδ T cells in the lungs and increased pulmonary Il17a mRNA expression and the number of IL-17A(+) CD45(+) cells in the lungs and these effects were abolished in TCRδ(−/−) mice. Ozone-induced increases in factors downstream of IL-17A signaling, including G-CSF, IL-6, IP-10 and KC were also decreased in TCRδ(−/−) versus wildtype mice. Neutralization of IL-17A during ozone exposure in wildtype mice mimicked the effects of γδ T cell deficiency. TNFR2 deficiency and etanercept, a TNFα antagonist, also reduced ozone-induced increases in Il17a mRNA, IL-17A(+) CD45(+) cells and BAL G-CSF as well as BAL neutrophils. TNFR2 deficient mice also had decreased ozone-induced increases in Ccl20, a chemoattractant for IL-17A(+) γδ T cells. Il17a mRNA and IL-17A(+) γδ T cells were also lower in obese Cpe(fat) versus lean WT mice exposed to subacute ozone, consistent with the reduced neutrophil recruitment observed in the obese mice. Taken together, our data indicate that pulmonary inflammation induced by subacute ozone requires γδ T cells and TNFα-dependent recruitment of IL-17A(+) γδ T cells to the lung.